PENGARUH VARIASI DOSIS KOAGULAN TERHADAP PERUBAHAN PARAMETER FISIKA – KIMIA KUALITAS AIR BAKU (Studi Kasus : PDAM Kota Samarinda) - Ali Murtopo; Aman Sentosa Panggabean; Idris Mandang (PROSIDING SEMINAR KIMIA, 2013)
This research was conducted with the aim of obtained the physical – chemical parameter change water quality caused by the coagulant dose variant. Issues raised in this study is a variation of the added coagulant dose on each raw water samples with dose of 5, 10, 15, 20, 25, 30, 35, 40, 45, 50, 55, and 60 ml. Raw water is obtained from Cendana Intake as much as 6 samples, and then the other raw water is obtained from Palaran Intake as much as 6 samples. Of each raw water sample obtained reported on the weather conditions, and ebb & flow river conditions at the time of data collect. Obtained data analyzed using anova test to find out the availability of influence resulting from coagulant dose variant : (a) Raw water turbidity parameter with a value F cal 33,61 and F table 1,82 (0,05), 2,32(0,01). Raw water color parameter with a value F cal 32,15 dan F table 1,82 (0,05), 2,32(0,01). Raw water pH parameter with a value F cal 260 dan F table 1,82 (0,05), 2,32(0,01). F cal value > F table value at all anova test for each parameter indicates that coagulant additions greatly affect turbidity and color parameters change derived raw water suitable standard PERMENKES/No.492/PER IV/2010 about drink water (turbidity 5 NTU and color 15 PtCo). While the addition of coagulant in the raw water will lower the pH of the water, up to add lime or soda ash to raise the pH. In total all raw water samples with turbidity 30 – 80 ppm each matching derived optimal dose distribution average as big 20 – 35 ppm.